The role of IL-1 in gout: from bench to bedside. (19th December 2017) - So, Alexander; Dumusc, Alexandre; Nasi, Sonia
Abstract: The translation of our knowledge of the biology of MSU crystal-induced IL-1 secretion gives rise to new targets and therapeutic strategies in the treatment of acute gout. The NACHT, LRR and PYD domains-containing protein 3 inflammasome is key to this, and is the subject of intense research. Novel pathways that modulate inflammasome activation, reactive oxygen species generation and extracellular processing of IL-1 have been described and show promise in in vitro and animal studies. Meanwhile, blocking IL-1 by various IL-1 inhibitors has shown the validity of this concept. Patients with acute gout treated with these inhibitors showed positive clinical and biological responses. More work needs to be performed to assess the risk/benefit profile of anti-IL-1 therapies as well as to identify those who will benefit the most from this novel approach to the treatment of gout.